Reduction of Selenite and Detoxification of Elemental Selenium by the Phototrophic Bacterium Rhodospirillum rubrum - Kessi, J. (American Society for Microbiology, 1999)
The effect of selenite on growth kinetics, the ability of cultures to reduce selenite, and the mechanism of detoxification of selenium were investigated by using Rhodospirillum rubrum. Anoxic photosynthetic cultures were able to completely reduce as much as 1.5 mM selenite, whereas in aerobic cultures a 0.5 mM selenite concentration was only reduced to about 0.375 mM. The presence of selenite in the culture medium strongly affected cell division. In the presence of a selenite concentration of 1.5 mM cultures reached final cell densities that were only about 15% of the control final cell density. The cell density remained nearly constant during the stationary phase for all of the selenite concentrations tested, showing that the cells were not severely damaged by the presence of selenite or elemental selenium. Particles containing elemental selenium were observed in the cytoplasm, which led to an increase in the buoyant density of the cells. Interestingly, the change in the buoyant density was reversed after selenite reduction was complete; the buoyant density of the cells returned to the buoyant density of the control cells. This demonstrated that R. rubrum expels elemental selenium across the plasma membrane and the cell wall. Accordingly, electron-dense particles were more numerous in the cells during the reduction phase than after the reduction phase.